El cuento y el aprendizaje de la comunicación en niños de la Institución Educativa Inicial N° 847 Nuestra Señora de la Purísima, Punchana 2022 - Mashacuri Jipa, Maruja Carmen (2024)
In the study it was formulated as a primary objective. To determine the relationship between the level of use of the story and the learning of communication in children of the Institución Educativa Inicial N°847 Nuestra Señora de la Purísima Punchana 2022, a quantitative, relational type of research was used, and the non-experimental research design was used. in a descriptive, cross-correlational way. The subjects that made up the population were all children of both sexes enrolled in the year 2022, which totaled 80 and the sample was census, to collect data, observation was used as a study technique, a guide as a means of obtaining information. The result obtained from the value of Spearman's Rho correlation coefficient between the story variables and children's communication learning is 0.352 and Sig. = 0.645, so the correlation between the two variables is moderate, therefore, it is accept the general hypothesis. There is a significant moderate relationship between the story and the learning of communication in the children of the Institución Educativa Inicial N°847 Nuestra Señora de la Purísima Punchana 2022.